Synthesis and characterization of iodosodalite. Issue 5 (7th March 2017) - Chong, Saehwa; Peterson, Jacob; Nam, Junghune; Riley, Brian; McCloy, John
Abstract: The effects of six process variables were investigated on the hydrothermal growth of iodosodalite, Na8 Al6 Si6 O24 I2 : pH (NaOH concentration), aging time, temperature, Al/Si ratio, precursors used (i.e., zeolite 4A, kaolinite, meta‐kaolin, colloidal silica, and sodium aluminate), and precursor concentration. Powder X‐ray diffraction (XRD) with Rietveld refinements, X‐ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM) were performed to characterize the structures, phase fractions, chemical state, and surface morphology of the synthesized products. Iodosodalite yield increased as aging time and pH increased. The crystallization of iodosodalite was favored in the temperature range 140°C‐180°C. Decreasing the Al/Si ratio by half increased the crystallization of basic cancrinite. Lowering the precursor concentration by adding water revealed the crystallization of nepheline hydrate I and a decrease in the sodalite fraction. Among the tested precursors, zeolite 4A yielded the highest mass fraction of iodosodalite in the synthesized powders. From the aging time and temperature variation experiments, the phase transformation of zeolite A→sodalite→cancrinite was observed. XPS and FTIR results showed the presence of only iodide but not iodate in the synthesized product. The crystallization of various minerals suggests that mechanisms for transport of the ions and formation of the aluminosilicate frameworks vary with hydrothermal conditions.